Modelling Approaches to Enhance the Quality of Forecasting Processes - Aziz, Rozainun Haji Abdul; Percy, D. F. (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2009)
The purpose of this paper is to put forward an insight into a mathematical model proposed in concept with the hope that both academicians and practitioners will progress in achieving forecast accuracy. The model explains the use of probability distribution against point forecasts, the cost function and fundamentals of Bayesian methodology in approach. Previous observations through pilot study, postal survey, case study and a follow-up survey form a basis in formulating the mathematical model explained. In writing this paper, we attempt to give explanations for and cost effects of imperfect forecasts, an oversight which frequently occurs to management.